2021
DOI: 10.55612/s-5002-047-006
|View full text |Cite
|
Sign up to set email alerts
|

Web-based videoconferencing for teaching online: Continuance intention to use in the post-COVID-19 period

Abstract: Web-based videoconferencing has gained a great momentum worldwide, with extremely high adoption rates during the COVID -19 pandemic. The current study aims to investigate the use of web-based videoconferencing for teaching in the post-COVID-19 landscape. The study proposes and evaluates a model to predict continuance intention to use videoconferencing systems, from the perspective of University teachers. The proposed model combines constructs from the Technology Acceptance Model (TAM) and the Expectancy Confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 56 publications
7
39
0
1
Order By: Relevance
“…This explained that the UTAUT and UTAUT-2 models were used to analyze user intentions in the education sector, information systems, e-commerce, and other technological fields (Tan, 2013;Cheung et al, 2018;Garg, 2021). Under these conditions, several experimental topics included (1) e-learning platforms (Alismaiel, 2021), (2) distance education platforms (Nikou, 2021), (3) multimedia learning-space stations, and (4) online communities (Liao et al, 2016). These studies indicated that when the use of urban-rural IWB became a habit, its effectiveness in improving students' abilities was subsequently enhanced.…”
Section: The Situation Of Interactive Whiteboard In Remote and Rural ...mentioning
confidence: 99%
“…This explained that the UTAUT and UTAUT-2 models were used to analyze user intentions in the education sector, information systems, e-commerce, and other technological fields (Tan, 2013;Cheung et al, 2018;Garg, 2021). Under these conditions, several experimental topics included (1) e-learning platforms (Alismaiel, 2021), (2) distance education platforms (Nikou, 2021), (3) multimedia learning-space stations, and (4) online communities (Liao et al, 2016). These studies indicated that when the use of urban-rural IWB became a habit, its effectiveness in improving students' abilities was subsequently enhanced.…”
Section: The Situation Of Interactive Whiteboard In Remote and Rural ...mentioning
confidence: 99%
“…The current small-scale study is aiming to contribute towards this direction. It is part of our larger project that investigates the impact of this online transition on teachers' and students' attitudes on technology enhanced learning [11].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, several empirical studies have shown that student satisfaction can be an essential determinant of continued use and full adoption of e-learning (Daneji et al, 2019;Lee, 2010;Lin et al, 2011;Nikou, 2021;Sørebø et al, 2009). Based on these studies, we can formulate the following hypothesis:…”
Section: Satisfactionmentioning
confidence: 98%
“…Furthermore, social influence positively impacts users' perceptions of the system's usefulness (Nikou, 2021;Nikou & Economides, 2017;Wu & Chen, 2017). Indeed, students who have never used e-learning as a learning approach before the COVID-19 pandemic may need to appreciate the opinions of their teachers, parents or others who influence their behavior.…”
Section: Social Influencementioning
confidence: 99%